In Situ Method for Determining Combination of Organic Compounds Interacting with Each Other on Silicon Oxide Surface. (1st January 2015) - Choi, Jaeha; Habuka, Hitoshi
Abstract : An experimental process for determining a combination of organic compounds, interacting with each other on a silicon oxide surface, was developed using a quartz crystal microbalance. The surface concentration of the four organic compounds, such as L-menthone (Mth), decylacetate (DA), diethylphthalate (DEP) and octanol (OCT), on a silicon oxide surface was evaluated in multi-component systems. The increase and decrease in the surface concentrations were not reversible with the changing gas phase concentrations in the two-component system consisting of Mth and DEP. Additionally, the small droplet shape of Mth placed on the DEP-coated glass plate surface was significantly different from that of DEP on the Mth-coated surface. Based on these results, Mth and DEP molecules were considered to have a significant interaction with each other.